Études Interculturelles De La Culture Indonésienne Et Française Dans Le Spot Publicitaire De Produit International - Oktaviani, Helda; Handayani, Sri (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2021)
Abstract Les diffÃƒÂ©rences entre la culture indonÃƒÂ©sienne et franÃƒÂ§aise font souvent un choc culturel aux apprenants de sorte quÃ¢â‚¬â„¢il est nÃƒÂ©cessaire dÃ¢â‚¬â„¢utiliser les mÃƒÂ©dias pour enseigner les connaissances interculturelles, dont lÃ¢â‚¬â„¢une est la publicitÃƒÂ© qui contiens des ÃƒÂ©lÃƒÂ©ments culturels. Les buts de cette ÃƒÂ©tude sont de dÃƒÂ©crire des ÃƒÂ©lÃƒÂ©ments de la culture indonÃƒÂ©sienne et franÃƒÂ§aise dans les publicitÃƒÂ©s et les similitudes et les diffÃƒÂ©rences entre les ÃƒÂ©lÃƒÂ©ments culturels indonÃƒÂ©siens et franÃƒÂ§ais. Cette ÃƒÂ©tude est une ÃƒÂ©tude descriptive qualitative. La mÃƒÂ©thode de documentation est le moyen de recueillir des donnÃƒÂ©es ÃƒÂ partir de cette ÃƒÂ©tude. Les rÃƒÂ©sultats de cette ÃƒÂ©tude montrent que quatre publicitÃƒÂ©s de produits internationaux version indonÃƒÂ©siens contiennent six ÃƒÂ©lÃƒÂ©ments culturels indonÃƒÂ©siens dans 24 extraits. Puis, sur les quatre publicitÃƒÂ©s de produits internationaux version franÃƒÂ§ais contiennent cinq ÃƒÂ©lÃƒÂ©ments culturels franÃƒÂ§ais qui ont ÃƒÂ©tÃƒÂ© trouvÃƒÂ©s dans 15. Les quatre paires de publicitÃƒÂ©s analysÃƒÂ©es contiennent les similitudes ainsi que les diffÃƒÂ©rences culturelles dans la vie quotidienne, les systÃƒÂ¨mes de connaissances, les systÃƒÂ¨mes de technologies et dÃ¢â‚¬â„¢ÃƒÂ©quipement vivant ainsi que les relations intra personnelles. Abstract Cultural differences often result in students experiencing a culture shock so it is necessary to use the media to teach cross-cultural knowledge, one of which is advertising containing cultural elements. The purpose of this study is to describe elements of Indonesian and French culture in advertising and to describe similarities and differences of cultural elements. The approach used in this study is descriptive qualitative. The documentation method is a way of collecting data from this study and the data is inserted into the data card. The data from these advertisements is analyzed by the technique of analyzing content. The results of the study showed that from the four Indonesian advertisements of international products, there were six cultural elements in 24 ad snippets. The four French advertisements of international products contained five cultural elements in 15 ad snippets. Of the four pairs of advertisements analyzed, the researcher found similarities as well as cultural differences in daily life, knowledge systems, living equipment systems and technologies as well as intrapersonal relationships